Effects of Increasing Salinity Stress and Decreasing Water Availability on Ecophysiological Traits of Quinoa (Chenopodium quinoa Willd.) Grown in a Mediterranean‐Type Agroecosystem. Issue 4 (4th December 2012) - Cocozza, C.; Pulvento, C.; Lavini, A.; Riccardi, M.; d'Andria, R.; Tognetti, R.
Abstract Quinoa is a native Andean crop for domestic consumption and market sale, widely investigated due to its nutritional composition and gluten‐free seeds. Leaf water potential (Ψleaf) and its components and stomatal conductance (gs) of quinoa, cultivar Titicaca, were investigated in Southern Italy, in field trials (2009 and 2010). This alternative crop was subjected to irrigation treatments, with the restitution of 100 %, 50 % and 25 % of the water necessary to replenish field capacity, with well water (100 W, 50 W, 25 W) and saline water (100 WS, 50 WS, 25 WS) with an electrical conductivity (ECw) of 22 dS m−1. As water and salt stress developed and Ψleaf decreased, the leaf osmotic potential (Ψπ) declined (below −2.05 MPa) to maintain turgor. Stomatal conductance decreased with the reduction in Ψleaf (with a steep drop at Ψleaf between −0.8 and 1.2 MPa) and Ψπ (with a steep drop at Ψπ between −1.2 and −1.4 MPa). Salt and drought stress, in both years, did not affect markedly the relationship between water potential components, RWC and gs. Leaf water potentials and gs were inversely related to water limitation and soil salinity experimentally imposed, showing exponential (Ψleaf and turgor pressure, Ψp, vs. gs) or linear (Ψleaf and Ψp vs. SWC) functions. At the end of the experiment, salt‐irrigated plants showed a severe drop in Ψleaf (below −2 MPa), resulting in stomatal closure through interactive effects of soil water availability and salt excess to control the loss of turgor in leaves. The effects of salinity and drought resulted in strict dependencies between RWC and water potential components, showing that regulating cellular water deficit and volume is a powerful mechanism for conserving cellular hydration under stress, resulting in osmotic adjustment at turgor loss. The extent of osmotic adjustment associated with drought was not reflected in Ψπ at full turgor. As soil was drying, the association between Ψleaf and SWC reflected the ability of quinoa to explore soil volume to continue extracting available water from the soil. However, leaf ABA content did not vary under concomitant salinity and drought stress conditions in 2009, while differing between 100 W and 100 WS in 2010. Quinoa showed good resistance to water and salt stress through stomatal responses and osmotic adjustments that played a role in the maintenance of a leaf turgor favourable to plant growth and preserved crop yield in cropping systems similar to those of Southern Italy.